2008
DOI: 10.1159/000151550
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Barrier Dysfunction, Endotoxemia, and Gastrointestinal Symptoms: The ‘Canary in the Coal Mine’ during Exercise-Heat Stress?

Abstract: Reduced intestinal blood flow and high intestinal temperatures during exercise-heat stress can lead to intestinal barrier dysfunction. Such dysfunction may increase intestinal permeability to endotoxin. During exercise-heat stress, intestinal barrier dysfunction and endotoxemia can produce gastrointestinal symptoms and increased production of pro-inflammatory cytokines. Such problems may be a warning sign ('canary in the coal mine') for the onset of exertional heat stroke. Failure to heed such a warning may cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 26 publications
2
85
0
8
Order By: Relevance
“…Systemically, changes in intestinal integrity were accompanied by an increase in circulating endotoxin. Increased circulating endotoxin during HS has been reported in several previous studies (Hall et al, 2001a;Lambert, 2008;Wang et al, 2011;Pearce et al, 2013b) and our current results fit with previous data. Interestingly, we also observed a decrease in circulating LBP.…”
Section: Discussionsupporting
confidence: 94%
“…Systemically, changes in intestinal integrity were accompanied by an increase in circulating endotoxin. Increased circulating endotoxin during HS has been reported in several previous studies (Hall et al, 2001a;Lambert, 2008;Wang et al, 2011;Pearce et al, 2013b) and our current results fit with previous data. Interestingly, we also observed a decrease in circulating LBP.…”
Section: Discussionsupporting
confidence: 94%
“…Physical variables were as follows: mean age: 25 y (range: 19-33 y); mean 6 SEM height: 1.78 6 0.02 m; body mass: 80. 1 (9), on day 25 of each arm to ensure the consistency of the 80% of the V : O 2 max protocol on days 2 and 14 ( Figures 1 and 2).…”
Section: Subjectsmentioning
confidence: 99%
“…One product that is already commercially available is zinc carnosine (ZnC), in which zinc and carnosine are linked in a polymeric one-to-one ratio, and is currently marketed as a zinc dietary supplement with "added value for gastric health." The combination of zinc with 1 The authors reported no funding received for this study. Colostrum was donated by Colostrum UK.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to dietary nutrients, systemic increases in intestinally derived endotoxin can be attributed to environmental and immunological Stressors. Hyperthennia increases intestinal permeability and, presumably, intestinal endotoxin transport (Lambert, 2004(Lambert, , 2008Pearce et al, 2011). Plasma antibodies to endotoxin are inversely related to growth in malnourished young children and are associated with increased intestinal permeability and systemic immune system activation (Campbell et al, 2003).…”
Section: Introductionmentioning
confidence: 99%